The necessary knowledge of military law in legal education - Pérez Villalobos, María Concepción (Revista Pedagogía Universitaria y Didáctica del Derecho, 2022)
In Spain, the university degree in Law does not include in its curriculum any subject related to Military Law. This article reflects the need to include it in the educational offer in order to provide law students with the necessary tools to complete their training and open up professional fields and expectations. It proposes the incorporation into the teaching guides of the subjects involved in this training and sets out the criteria that lead to this change in the study plans. This is an innovative proposal that standardizes the study of an important sector of the legal system under the premises of a normative Constitution such as the Spanish Constitution of 1978.